Vaccination in rheumatology (the 2019 update of EULAR recommendations) - B. S. Belov; G. M. Tarasova; N. V. Muravyevа (Научно-практическая ревматология, 2019)
In modern rheumatology, comorbid infections have a significant impact on morbidity and mortality, especially in immuneinflammatory rheumatic diseases (IRDs). One of the ways to solve this problem is to study and actively use various vaccines. This paper analyzes the 2019 updated version of the European League Against Rheumatism (EULAR) recommendations for vaccination in adult patients with IRDs. It discusses the safety and immunogenicity of vaccination associated with the prevention of various infections in patients with IRDs. The basic directions of future investigations on this problem are outlined.